Medical Students View about the Integrated MBBS Course: A Questionnaire Based Cross-sectional Survey from a Medical College of Kathmandu Valley - Banerjee, Indrajit; Jauhari, Akhilesh Chandra; Johorey, Ajay Chandra; Bista, Durga; Roy, Bedanta; Sathian, Brijesh (Nepal Journal of Epidemiology, 2011)
Background Accreditation of curriculum by students may be useful in further modification of teaching and learning methods in medical colleges of any country specially Nepal. Course curriculum of medical sciences is made by learned professors of Universities, politicians and the government officers without consulting the students for whom it is made. In Nepal, Medical education is an experimental integrated teaching of four and half years for MBBS degree. Until now it has not been assessed as to what type of Doctors we are producing. This paper aims on the objective to find out whether integrated teaching or classical medical studies produce better doctors. Methods The present study was done to assess the teaching, learning and evaluation procedures adopted in Nepal Medical College, Kathmandu by getting feedback from students of 4th (Basic Sciences), 5th-7th semesters and feedback was also taken from a few final year students (Clinical Sciences). A total of nearly two hundred students from this institution participated in this study. A multi-graded questionnaire was prepared and a pilot study of 20 students was done and the results were discussed among the authors to modify the questionnaire. This modified questionnaire was used in the main study. The same questionnaire was used for eliciting feedback from clinical students. The present study was undertaken from August 2008-January 2009. Results Out of 200 medical students, the mean age was found to be 19.4 ± 3 years SD. In gender distribution, male students (61%) were higher than female students (39%). Most of the medical students (70%) wanted to become doctor, to become rich and famous, 90% wanted to go to US (Massive brain drain). 90% of the students perceived that Anatomy is the most interesting and most relevant basic science subject for clinical studies and in Anatomy theory hours of teaching is to be increased (60%). Community Medicine was the most uninteresting subject of Basic sciences and if they are assured of attendance which subject they would not like to attend community medicine classes. 85% wanted that Pharmacology should be reduced in first four semesters and should be extended to seventh semester like Community Medicine. The best teaching method is Chalk and Board Method (60%) and followed by LCD slides (20%). Conclusion: Overall the results were alarming and may be taken up seriously by the policy makers. They can bring about amendments in course curriculum of universities in future. Keywords: Medical Education; Under-graduate; Post- Graduate; Nepal Medical College. DOI: http://dx.doi.org/10.3126/nje.v1i3.5575 Nepal Journal of Epidemiology 2011;1(3) 95-100